Growth and anatomical adaptations in response to salinity stress in Cucurbita moschata Duchesne ‘Butternut’ (Cucurbitaceae) - Worasitikulya Taratima,; Sununta Sudjai,; Pitakpong Maneerattanarungroj, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Pumpkin or squash is an economically important crop that is moderately sensitive to salinity but how its growth is affected by soil salinity is poorly understood. Salinity stress on physiological and anatomical traits of Cucurbita moschata ‘Butternut’ was investigated under hydroponic culture using Hoagland’s solution with various NaCl concentrations (0, 25, 50, 75, 100, and 150 mM) for four weeks. The results showed that pumpkin growth characters decreased after cultured in various NaCl concentrations. Leaf number, leaf width, leaf length, root number, stem height, stem diameter, green intensity in terms of SPAD units, chlorophyll fluorescence (Fv’/Fm’, Fv/Fm), total chlorophyll, chlorophyll a and chlorophyll b contents significantly (p < 0.05) decreased after culture in various NaCl concentrations. Salinity stress impacted fiber layer thickness, vascular bundle size and vessel diameter of treated plants but did not affect cuticle thickness. Physiological and anatomical traits significantly correlated with salinity gradients, except for chlorophyll b and chlorophyll fluorescence, in both light and dark condition. Results provide significant data to improve the understanding of adaptation mechanisms of tolerant pumpkin cultivars under salinity stress condition.